Delivery of CD47 blocker SIRPα-Fc by CAR-T cells enhances antitumor efficacy. Issue 2 (2nd February 2022) - Chen, Huanpeng; Yang, Yuying; Deng, Yuqing; Wei, Fengjiao; Zhao, Qingyu; Liu, Yongqi; Liu, Zhonghua; Yu, Bolan; Huang, Zhaofeng
Abstract : Background: Chimeric antigen receptor (CAR) T cell therapy has been successfully applied in treating lymphoma malignancies, but not in solid tumors. CD47 is highly expressed on tumor cells and its overexpression is believed to inhibit phagocytosis by macrophages and dendritic cells. Given the antitumor activity against preclinical model of CD47-blocking to induce the innate and adaptive immune system in the tumor microenvironment, here we developed a CAR-T cell secreting CD47 blocker signal regulatory protein α (SIRPα)-Fc fusion protein (Sirf CAR-T) to boost CAR-T cell therapeutic effect in solid tumor therapy. Methods: Murine T cells were transduced to express a conventional anti-Trop2 CAR and Sirf CAR. The expression of SIRPα-Fc fusion protein in the supernatant of CAR-T cells and its effect on macrophage phagocytosis were tested in vitro. In vivo antitumor efficacy of CAR-T cells was evaluated in immunocompetent mice and analysis of the tumor microenvironment in the tumor-bearing mice was performed. Results: We found that Sirf CAR-T cells dramatically decreased tumor burden and significantly prolonged survival in several syngeneic immunocompetent tumor models. Furthermore, we found that Sirf CAR-T cells induced more central memory T cells (TCM ) and improved the persistence of CAR-T cells in tumor tissue, as well as decreased PD-1 expression on the CAR-T cell surface. In addition, we demonstrated that Sirf CAR-T cells could modulate the tumor microenvironment by decreasing myeloid-derived stem cells as well as increasing CD11c + dendritic cells and M1-type macrophages in tumor tissue. Conclusions: In summary, our findings indicate that CD47 blocker SIRPα-Fc enhances the antitumor efficacy of CAR-T cells and propose to block CD47/SIRPα signaling effect on CAR-T cells function, which could provide a new strategy for successful cancer immunotherapy by rationalizing combination of CD47 blocker and CAR-T cell therapy.